Maraknya Geng Motor yang Meresahkan Warga Bandung Hingga Berujung Pembacokan - Ageng Saepudin Kanda; Septiani Septiani (Global Leadership Organizational Research in Management, 2024)
This article contains descriptive research on juvenile delinquency. This report was created to fulfill the assignment requirements for the Research Methodology course at the Digital Technology University. This scientific work provides guidance in learning how important it is for us to learn and choose a good social environment for teenagers and not be separated from the guidance and direction of parents..